Innovations in Intelligent Image Analysis - Kwasnicka, Halina; Jain, Lakhmi C. (Studies in Computational Intelligence, 2011)
This book presents an introduction to new and important research in the images processing and analysis area. It is hoped that this book will be useful for scientists and students involved in many aspects of image analysis. The book does not attempt to cover all of the aspects of Computer Vision, but the chapters do present some state of the art examples.